PENGARUH PENGGUNAAN MEDIA FLASH TERHADAP HASIL BELAJAR SISWA PADA MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT - Setiani, Dini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe research to determine the effect of learning with flash media on the material of electrolyte and non electrolyte solution to student learning result of class X MAN 2 Filial Pontianak. The research technique used quasi experimental design method                  Non-Equivalent Control Group Design. Research subjects obtained students X A and X B with saturated sampling technique which amounted to 42 students. Data collection techniques in this study are measurement techniques and direct communication techniques. The data collection tool used is the test of learning outcomes. The results tested hypothesis using Test Equals Variances Assumed with α = 95% obtained Z arithmetic of 0.035, is in the acceptance area Ha. This shows that there is a significant difference between the learning outcomes of students who were given learning using Flash Media with learning without using Flash Media. Learning using Flash Media gives effect with the effect size price of 0.31 (medium category). Keyword: Influence, Flash Media, learning outcomes,  electrolyte and non electrolyte solutions